Gelu Epen Culture: Rationality Of The Local Wisdom-Based People's Market Revitalization Program - Lamawuran, Yosef Dionisius; Ratumakin, Paulus Adrianus Kopong Liat; Molan, Kristianus Simon Hale; Tokan, Frans Bapa; Susu, Mikael Thomas (JURNAL TRIAS POLITIKA, 2025)
This study was designed with a focus on the adoption of Indigenous Public Administration (IPA) values in the development of Indonesian public administration theory and practice, especially in the economic policy sector. This study aims to evaluate and critique the practice of Western Public Administration (WPA) in implementing the traditional market revitalization program and describe the local wisdom value of Gelu Epen practice as a revitalization model. The method used is qualitative with a descriptive approach. Data collection techniques through interviews, observations and documentation. Data analysis techniques are carried out by data reduction, data presentation and drawing conclusions. This study found four important things. First, the traditional market revitalization program by the government is often criticized for focusing on organizing and developing market buildings, rather than improving the economy, organizing market management and preserving local cultural heritage. Second, the factors causing the failure of the revitalization program include: the intervention of WPA practices, strong government dominance and the neglect of participation from local social and economic institutions. Third, the success of the revitalization of the Waiwuring traditional market cannot be separated from the government's efforts to revive the Gelu Epen (barter) tradition which is a local cultural heritage of Lamaholot. Fourth, the values, norms and principles of Gelu Epen practice such as equality or justice (Ha'ma), mutual trust (No Keni'ine), kinship (Haba Breun) and tolerance (Onga Arep), are maintained to maintain the achievement of the economic and social functions of the Waiwuring market.